Project-Based Learning in Arabic Speaking Instruction: Students’ Perceptions from a Muhadatsah Course in Higher Education - Sugirma Sugirma; M. Abdul Hamid; Zakiyah Arifa (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Developing speaking proficiency remains a major challenge in Arabic language education, particularly in foreign language contexts where students often face limited opportunities for authentic communication and low confidence in oral interaction. Although Project-Based Learning (PjBL) has been widely promoted as a student-centered approach for enhancing communicative engagement, existing studies have predominantly focused on learning outcomes or technological integration, with limited attention to how learners experience project-based speaking instruction in Arabic classrooms. Addressing this gap, the present study investigates students’ perceptions of the implementation of Project-Based Learning in Arabic speaking instruction within a Muhadatsah course. This study employed a qualitative case study design involving twelve undergraduate students in the Arabic Education Program at IAIN Ternate during the 2024/2025 academic year. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns in students’ experiences during the project-based learning process. The analysis identified six interconnected dimensions shaping students’ learning experiences: increased speaking confidence through repeated communicative practice, active participation in project tasks, collaborative peer interaction, technology-supported rehearsal and reflection, contextualized linguistic development, and the emergence of creativity and problem-solving skills. These findings suggest that PjBL functions as an integrated learning environment that simultaneously supports communicative practice, learner engagement, and reflective language use. However, the findings are limited to a single institutional context and rely primarily on students’ perceptions. Future research should examine project-based speaking instruction across diverse educational settings and incorporate mixed-method approaches to assess its impact on measurable speaking proficiency development.